A teaching–learning method based on CFD assisted with matlab programming for hydraulic machinery courses. Issue 4 (18th January 2012) - Vicéns, J. L.; Zamora, B.
ABSTRACT This article presents a teaching–learning methodology for the course "Hydropower and Ocean Power" in the Master of Renewable Energy Program at the Technical University of Cartagena (Spain). In line with the famous "Bologna Declaration, " a new teaching approach is proposed, in order to ensure that students acquire skills related to the ability of analyzing and designing Hydraulic Machinery. The roles of the tutor facilitator, as well as the use of freehand sketches and the Matlab programming to optimize the management of commercial CFD packages, are some specific features of the project.© 2012 Wiley Periodicals, Inc. Comput Appl Eng Educ 22:630–638, 2014; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.21554